Students’ perceptions of schools’ influence on the leadership self-efficacy of adolescent girls: religious and secular post-primary schools in Israel - Perets, Shenhav; Davidovitch, Nitza; Lewin, Eyal (Frontiers in Psychology, 2025)
The aim of this study is to evaluate the perceived effect post-primary school has on female teenagers’ leadership self-efficacy according to their own perceptions. The study employs social cognitive theory and focuses on the teenagers’ personal social experiences and perceptions regarding the way leadership is taught in their schools. The research is based on 26 in-depth interviews among teenage girls attending middle and high schools in the public education system in Israel. The teenage girls attend secular state education schools and religious all-girl state education schools (Ulpana). The findings indicate four major ways in which self-efficacy can be developed. The religious all-girl schools seem to promote leadership self-efficacy more effectively than secular mixed-gender schools, primarily by mastering leadership experiences, social modeling, and social persuasion of leadership ability.